2022
DOI: 10.3389/fphar.2022.873792
|View full text |Cite
|
Sign up to set email alerts
|

Targeting GGT1 Eliminates the Tumor-Promoting Effect and Enhanced Immunosuppressive Function of Myeloid-Derived Suppressor Cells Caused by G-CSF

Abstract: Myeloid-derived suppressor cells (MDSCs) are major immunosuppressive cells that accumulate in tumor-bearing hosts. Since MDSCs suppress anti-tumor immunity and promote tumor progression, they are promising targets for cancer immunotherapy. Granulocyte colony-stimulating factor (G-CSF) is an agent used for the treatment of chemotherapy-induced febrile neutropenia (FN) in patients with cancer. However, several reports have revealed that G-CSF plays crucial immune-related adverse roles in tumor progression throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…GGT increases the level of intracellular glutathione, which can promote tumor cells to maintain balance in reactive oxygen species and avoid cell death through redox pathways during pro-oxidant therapy ( 33 ), GGT-positive tumors possess stronger proliferative ability and drug resistance ( 34 , 35 ). Researchers have demonstrated that granulocyte colony-stimulating factor (G-CSF) upregulates GGT1 and enhances the immunosuppressive function of myeloid-derived suppressor cells, and GGT inhibitors can alleviate tumor immunosuppression and the tumor-promoting effect of G-CSF ( 36 ). Alkaline phosphatase is ubiquitous expressed in human body, which has four types: intestinal ALP, placental ALP, germ cell ALP and single tissue non-specific ALP ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…GGT increases the level of intracellular glutathione, which can promote tumor cells to maintain balance in reactive oxygen species and avoid cell death through redox pathways during pro-oxidant therapy ( 33 ), GGT-positive tumors possess stronger proliferative ability and drug resistance ( 34 , 35 ). Researchers have demonstrated that granulocyte colony-stimulating factor (G-CSF) upregulates GGT1 and enhances the immunosuppressive function of myeloid-derived suppressor cells, and GGT inhibitors can alleviate tumor immunosuppression and the tumor-promoting effect of G-CSF ( 36 ). Alkaline phosphatase is ubiquitous expressed in human body, which has four types: intestinal ALP, placental ALP, germ cell ALP and single tissue non-specific ALP ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…To verify the direct effect of MDSCs on poly(I:C)-induced lung inflammation, in vitro MDSCs were adoptively transferred into mice in an intravenous manner and the consequences of inflammation were studied. In vitro MDSCs were differentiated from BM cells with GM-CSF stimulation, as described previously (CD11b + Gr-1 + MDSC purity over 90%, Figure S5A ) ( 35 , 36 ). These cells displayed higher Arg1 , Nos2 , and Cybb expression than BM cells ( Figure S5B ) and potently inhibited CD8 + T-cell proliferation ( Figure S5C ).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of gene expression profiles showed that glutathione metabolism was the pathway responsible for the enhanced immunosuppressive ability of 6G − BM-MDSC. We previously showed that glutamate, one of the metabolites of glutathione, would enhance the immunosuppressive function of MDSCs [ 14 ]. In addition, we found that glutamate signaling through metabotropic glutamate receptor 2/3 enhances the immunosuppressive ability of MDSCs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, they listed some clinical cases that used GM-CSF to rescue tumor therapy-induced neutropenia. We previously reported that G-CSF, which is used for the prevention and therapy for neutropenia, enhanced the immunosuppressive activity of MDSCs through the glutathione degradation pathway, leading to tumor progression [ 14 ]; therefore, GM-CSF might also do so. Although further in vivo cancer model studies are needed, our findings indicated that such GM-CSF treatment might lead to the differentiation of stronger immunosuppressive MDSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation